Application of K-Means Algorithm Data Mining in Goat Meat Production Data Grouping in Indonesia - Mochamad Wahyudi; Solikhun Solikhun; Lise Pujiastuti (Jurnal Mantik, 2022)
Data mining is the process of mining data from big data to get important information. The data mining process requires the use of artificial intelligence technology. The production of goat meat is very much needed in the fulfillment of protein ingredients for the people of Indonesia. It is necessary to make a grouping of goat meat production to see the condition of the map of the strength of meat production in Indonesia, so that the government can take appropriate steps to develop goat meat production in Indonesia. This study uses data mining techniques using the k-means clustering method to classify goat meat production in Indonesia. The results of this study are data on mutton product clustering, namely 2 nodes in the high group, the low group having 22 nodes, and the medium group having 10 nodes.